2014
DOI: 10.1002/jeab.97
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons' delay discounting functions established using a concurrent‐chains procedure

Abstract: Several studies have examined discounting by pigeons and rats using concurrent-chains procedures, but the results have been inconsistent. None of these studies, however, has established that discounting functions derived from estimates of indifference points can be obtained with a concurrent-chains procedure, so their validity remains in doubt. The present study used a concurrent-chains procedure within sessions combined with an adjusting-amount procedure across sessions to determine the present, subjective va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 60 publications
1
41
1
1
Order By: Relevance
“…Pigeons failed to show a magnitude effect also when tested in a two-component concurrent-chains procedure, in which they could choose between a ''small amount component'', leading to a relatively brief access to food, and a ''large amount component'', leading to a 2.5 times longer access to food across different delay conditions (Grace 1999). Similar results were obtained when pigeons were tested with a novel paradigm combining a concurrent-chains procedure and an adjusting-amount procedure (Oliveira et al 2014). Also, common marmosets and cotton-top tamarins tested in a spatial discounting task (in which they chose between a smaller closer option and a larger distant option) did not show any raise in preference for the larger option when reward magnitude was increased (Stevens et al 2005).…”
Section: Introductionsupporting
confidence: 75%
“…Pigeons failed to show a magnitude effect also when tested in a two-component concurrent-chains procedure, in which they could choose between a ''small amount component'', leading to a relatively brief access to food, and a ''large amount component'', leading to a 2.5 times longer access to food across different delay conditions (Grace 1999). Similar results were obtained when pigeons were tested with a novel paradigm combining a concurrent-chains procedure and an adjusting-amount procedure (Oliveira et al 2014). Also, common marmosets and cotton-top tamarins tested in a spatial discounting task (in which they chose between a smaller closer option and a larger distant option) did not show any raise in preference for the larger option when reward magnitude was increased (Stevens et al 2005).…”
Section: Introductionsupporting
confidence: 75%
“…We concluded that LEWs are more adaptable to dynamic changes in the contingencies of reinforcement than are F344s, and that impulsivity is an advantage in dynamic reinforcing environments that might be adaptive for both human and nonhuman animals (Fawcett et al, 2012). As has recently been noted, concurrent-chains procedures have distinct advantages over the techniques typically used to study delay discounting, and they can be used without worrying that new discoveries can be accredited to the use of innovative techniques (Oliveira, Green, & Myerson, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Because responses at the 0-s delay determine the intercept ( A parameter) of the exponential function, this accounts for the ceiling effect observed with this parameter. One method that can circumvent this limitation is the used of a concurrent-chains procedure, which ensures subjects cannot exclusively respond for one alternative (see Aparicio et al 2015; Oliveira et al 2014 for a detailed description of the concurrent-chains procedure).…”
Section: Discussionmentioning
confidence: 99%